Impact of Working from Home on Cardiovascular Health: An Emerging Issue with the COVID-19 Pandemic - Stefania Angela Di Fusco (MDPI AG, 2021)
Mandatory working from home is one of the consequences of the COVID-19 pandemic for a large number of workers. Transition to working from home may significantly impact lifestyle, psychosocial status, and the overall health of workers. This review summarizes available data about the effects of lockdown measures, particularly working from home, on cardiovascular risk factors including sedentary lifestyle, unhealthy diet pattern, psychological distress, smoking, alcohol misuse, and cardiometabolic parameters. Finally, we suggest countermeasures that can attenuate the negative health impact of working from home. Indeed, timely and tailored interventions implemented by companies in cooperation with the health care system could allow workers to benefit more from some of the advantages associated with working from home.